A rare case of oral metastasis of renal clear cell carcinoma: case report and review of literature - Kovalski, Luan Nathiel Santana; Ribeiro, Julia Turra; Martins, Manoela Domingues; Oliveira, Marcia Gaiger De; Rivero, Luis Fernando; Carrard, Vinicius Coelho; Martins, Marco Antonio Trevizani (Journal of Oral Diagnosis, 2020)
This is a case report of metastasis of renal clear cell carcinoma, a very rare malignant neoplasia, in the oral cavity. The patient went to the oral medicine clinic complaining of a nodule in the left upper gingival region that had started a month previously. Clinical evaluation revealed a large, red and bleeding nodule in the superior gingiva of the left side of the maxilla. A panoramic radiographic revealed alveolar bone destruction. Incisional biopsy was performed, and microscopic evaluation revealed an unspecified malignant neo- plasia. The patient was referred to a local hospital for investigation. A systemic evaluation showed a large nodule in the right kidney, another nodule in the liver, small nodules in both lungs and two nodules in the brain. A biopsy of the right kidney was performed, showing a renal clear cell carcinoma. After that, new immunohistochemical analysis of the oral lesion was performed demonstrating it to be one more implant of renal neopla- sia. The final diagnosis was renal clear cell carcinoma, with metastases in the liver, lung, mouth and nervous system. Unfortunately, the patient died six months after the diagnosis. The primary tumour was only discovered due to the oral manifestation of the disease, emphasising the importance of oral medicine in the diagnosis of metastatic lesions.